An evaluation of the English language teaching and learning materials for students of Information Technology at a public university in Hanoi - Ngô Thị Quỳnh
Thesis presented literature review: Materials in english language teaching and learning, material evaluation. Research methodology: Research design, participants, data collection instruments, data colection procedure. Findings and discussions